Analisis Partisipasi Dan Sikap Politik Masyarakat Dalam Pemilihan Presiden 2019 Di Kabupaten Bangkalan - Abdullahdil Hanani; Sunardjo; Anindita Trinura Novitasari (Penerbit STKIP PGRI Bangkalan, 2019)
The presidential election is a form of democratic party in a country to elect a head of state who will carry out state policies within a period of leadership which must be held accountable to the people. Presidential Elections in Indonesia are carried out based on the principle of direct, general, free and confidential (Luber), Honest and Fair (Jurdil). The people choose directly who will be the head of state (President and Vice President). (1945 Constitution concerning presidential elections and terms of office for president and vice president). Political Participation Is Determination of the attitude of participation or involvement and role of an Individual, so that in the end ting is to give the right to vote for one of the presidential candidates to participate in determining the head of state (president) in the next five years, and also to avoid abstentions. encourages the individual to support and vote during the presidential election, Participation supports here in the form of participating and involved in campaigning, and voicing the vision and mission of one of the candidates in the presidential election While participating in vo Political attitude is an attitude that gives an individual voice in determining a leader, which is absolutely essential for the community to give rights as regulated in the 1945 law in articles 27ayat (1) and (2); article 28, article 28D paragraph (3), article 28E paragraph (3). In this law it is emphasized that the State must fulfill the rights of its citizens, especially in democratic parties, especially in the presidential election, whose leadership holds office for one period (five years).